Seismic Discrimination of Controlled Explosions and Earthquakes Near Mount St. Helens Using P/S Ratios. Issue 10 (28th September 2020) - Wang, Ruijia; Schmandt, Brandon; Kiser, Eric
Abstract: Explosions and earthquakes are effectively discriminated by P / S amplitude ratios for moderate magnitude events (M ≥ 4) observed at regional to teleseismic distances (≥200 km). It is less clear if P / S ratios are effective explosion discriminants for lower magnitudes observed at shorter distances. We report new tests of P / S discrimination using a dense seismic array in a continental volcanic arc setting near Mount St. Helens, with 23 single‐fired borehole explosions (ML 0.9–2.3) and 406 earthquakes (ML 1–3.3). The array provides up to 95 three‐component broadband seismographs, and most source‐receiver distances are <120 km. Additional insight is provided by ~3, 000 vertical component geophone recordings of each explosion. Potential controls on local distance P / S ratios are investigated, including frequency range, distance, magnitude, source depth, number of seismographs, and site effects. A frequency band of about 10–18 Hz performs better than lower or narrower bands because explosion‐induced S wave amplitudes diminish relative to P for higher frequencies. Source depth and magnitude exhibited weak influences on P / S ratios. Site responses for earthquakes and explosions are correlated with each other and with shallow crustal V p and V s from traveltime tomography. Overall, the results indicate high potential for local distance P / S explosion discrimination in a continental volcanic arc setting, with ≥98% true positives and ≤6.3% false positives when using the array median from ≥16 stations. Performance is reduced for smaller arrays, especially those with ≤4 stations, thereby emphasizing the importance of array data for discrimination of low magnitude explosions. Plain Language Summary: Methods to remotely classify seismic sources as either shear‐slip earthquakes or shallow subsurface explosions are important geophysical tools. They are used for investigations of anthropogenic processes such as underground nuclear explosion tests and mining activity as well as to obtain pure catalogs of tectonic and volcanic earthquakes. The ratio of compressional ( P ) wave amplitude to shear ( S ) wave amplitude is effective for classifying large earthquakes and explosions observed hundreds to thousands of kilometers away. Application of such methods at local distances is a topic of growing interest because smaller magnitude sources are only observed at close distances. We tested influences on P / S amplitude ratios and their effectiveness for source discrimination using a data set of tectonic and volcanic earthquakes and controlled shallow borehole explosions near Mount St. Helens. Most observations were within 120 km. We found that use of high frequencies and array‐median statistics is largely effective for source discrimination in this setting, successfully classifying 100% of explosions while falsely attributing about 5% of earthquakes to explosions. Variability of P / S ratios across the seismic array has a highly similar pattern for explosions and earthquakes and that pattern appears to be controlled by the seismic velocity structure of the shallow crust. Key Points: Influences on local P / S ratios are analyzed with 23 shallowly buried explosions and 406 ML  ≥ 1 earthquakes near Mount St. Helens Optimized array‐median P / S ratios achieve ≥98% true positives and ≤6.3% false positives when using ≥16 stations to classify explosions P / S ratio variations at individual stations are interpreted as site effects that correlate with shallow crustal velocity structure